A Temporal White Noise Analysis for Extracting the Impulse Response Function of the Human Electroretinogram - Zele, Andrew J.; Feigl, Beatrix; Kambhampati, Pradeep K.; Aher, Avinash; Mckeefry, Declan; Parry, Neil; Maguire, John; Murray, Ian; Kremers, Jan (Translational Vision Science & Technology, 2017)
Purpose: We introduce a method for determining the impulse response function (IRF) of the ERG derived from responses to temporal white noise (TWN) stimuli.Methods: This white noise ERG (wnERG) was recorded in participants with normal trichromatic vision to full-field (Ganzfeld) and 39.3 degrees diameter focal stimuli at mesopic and photopic mean luminances and at different TWN contrasts. The IRF was obtained by cross-correlating the TWN stimulus with the wnERG.Results: We show that wnERG recordings are highly repeatable, with good signal-tonoise ratio, and do not lead to blink artifacts. The wnERG resembles a flash ERG waveform with an initial negativity (N1) followed by a positivity (P1), with amplitudes that are linearly related to stimulus contrast. These N1 and N1-P1 components showed commonalties in implicit times with the a-and b-waves of flash ERGs. There was a clear transition from rod-to cone-driven wnERGs at similar to 1 photopic cd.m(-2). We infer that oscillatory potentials found with the flash ERG, but not the wnERG, may reflect retinal nonlinearities due to the compression of energy into a short time period during a stimulus flash.Conclusion: The wnERG provides a new approach to study the physiology of the retina using a stimulation method with adaptation and contrast conditions similar to natural scenes to allow for independent variation of stimulus strength and mean luminance, which is not possible with the conventional flash ERG.
Keywords: electroretinogram (ERG); temporal white noise; impulse response function